(untitled) (Szociológiai Szemle, 2024)
In the Third World the urban unemployment is a reflexion of the rural one - say their experts. We try to interprete the present East-Central-European unemployment according of this pattern, and made our investigations in a little region of Transylvania on family-farms. There we found: - families are working in a very broad dividing of labour with relatives and neighbours; - they produce dominantly for own needs, and sell only few surpluses; - their taking urban/industrial employments plays only a supplementary role in supporting the family and its farming.